PEMANFAATAN TANDAN KOSONG SAWIT UNTUK PUPUK ORGANIK PADA INTERCROPPING KELAPA SAWIT DAN JAGUNG - Muhammad Hatta; Jafri ;; Dadan Permana (Balai Besar Pengkajian dan Pengembangan Teknologi Pertanian, 2014)
Utilization of Oil Palm Empty Fruits Bunches for Organic Fertilizer on Intercropping of Oil Palm and Maize. Processing of crude palm oil resulted a waste of empty fruit bunches that have not been optimally utilized by most of oil palm factories in West Kalimantan. Its waste was processed to be compost using bio activator, which made the process faster. This compost consists of high macronutrients (N, P, K, Mg, Ca), thus could be used for organic fertilizer. This organic fertilizer was utilized to optimize the land of oil palm plantation with intercropping pattern of immature oil palm and maize. The purpose of this study was to determine the response of application of compost from oil palm empty fruit bunches towards growth of oil palm and yield of maize on intercropping pattern. The research was conducted by composting of oil palm empty fruit bunches with the commercial bio activator then implemented them to the intercropping pattern of immature oil palm plantation and maize. The experimental design used was a randomized block design with four fertilizer treatment and was repeated five times. Results of the study showed that the use of oil palm empty fruit bunches with a dose of 150 kg per plant for palm and 6 t/ha for maize with intercropping patterns to increase of 20 cm height plant for palm during 10 month and provide maize yields of 6.8 t/ha. Results of the financial analysis of maize crop showed profit of IDR 14.278.000/ha/season. Key words: Waste, oil palm empty fruit bunches, composting, intercropping, maize, added valuePengolahan Crude Palm Oil selalu menghasilkan limbah tandan kosong kelapa sawit dan belum dimanfaatkan secara optimal oleh sebagian besar Pabrik Kelapa Sawit di Kalimantan Barat. Limbah tersebut dapat diproses menjadi kompos dengan menggunakan bioaktivator dalam waktu yang lebih cepat. Kandungan unsur hara makro (N, P, K, Mg, Ca) pada limbah tandan kosong sawit cukup tinggi dan dapat digunakan sebagai pupuk organik. Pupuk organik ini dapat dimanfaatkan untuk optimalisasi lahan perkebunan kelapa sawit dengan pola intercropping antara tanaman kelapa sawit yang masih muda dengan tanaman jagung. Tujuan pengkajian ini adalah untuk mengetahui respon aplikasi kompos tandan kosong sawit hasil dekomposisi bioaktivator komersial terhadap pertumbuhan tanaman kelapa sawit dan hasil jagung dengan pola tanam intercropping. Pengkajian dilakukan dengan pembuatan kompos tandan kosong sawit menggunakan bioaktivator komersial yang diaplikasikan terhadap pola tanam intercropping tanaman kelapa sawit belum menghasilkan dengan tanaman jagung. Rancangan yang digunakan adalah Rancangan Acak Kelompok dengan 4 perlakuan pemupukan kompos tandan kosong sawit diulang 5 kali. Hasil kajian menunjukkan pemberian kompos tandan kosong sawit dengan dosis 150 kg/tanaman untuk kelapa sawit dan 6 t/ha untuk tanaman jagung dengan pola intercropping dapat meningkatkan tinggi tanaman kelapa sawit 20 cm selama 10 bulan dan memberikan hasil jagung sebanyak 6,8 t/ ha, menghasilkan keuntungan sebesar Rp14.278.000,-/ha/musim. Kata kunci : Limbah, tandan kosong sawit, kompos, intercropping, jagung, nilai tambah